The Laffer Curve in the Czech Republic - Haufer, Tomáš; Potužák, Pavel; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
Taxation is a frequent and important topic of discussion in politics, economics and the public debate as well. This thesis analyses the overall tax system, the Personal Income Tax and the Corporate Income Tax from the Laffer Curve perspective with the objective of finding a revenue-maximising tax rate for each of the mentioned. Because of the non-stationarity of some data, two branches of models are estimated. One takes the stationarity as an assumption and finds the revenue-maximising rates at 28.6% for the overall tax system, 17.5% for the Personal Income Tax, and 27.5% for the Corporate Income Tax. The second branch finds linear relationships between the growth rates of the tax revenues and the growth rates of the tax rates, which are all stationary. Three methods are utilised for the estimation, Ordinary Least Squares, Two Stage Least Squares with Instrumental Variables, and the Generalised Method of Moments. The thesis uses quarterly data from 1996 Q1 to 2023 Q4. Comments on other determinants of tax revenues accompany the main findings. The research presented in this thesis provides the latest empirical evidence on the relationship between tax rates, macroeconomic factors, and their impact on tax revenues in the Czech Republic.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses